MOTRIC ROLE IN ADDRESSING THE EXERCISE OF A CATEGORY III OF GYMNASTICS - Vilcu, Dumitru (Arena-Journal of Physical Activities, 2013)
This writing refers to the specific ways that the teacher of physical education uses during classes to physically prepare the students in the gymnasium cycle. Gymnastics is one of the most important branches of physical education. Having an extremely valuable content and a huge variety of methods, it accomplishes an essential role in harmonious physical development and specific motrical skills.